EKSPEKTASI KARIER MAHASISWA GEN Z DALAM INDUSTRI PERKREDITAN - Faujiah, Nabila; Hatimatunnisani, Hani; NurFauziah, Raisya Fadillah; Pintu Batu, Shintya Rosalina; Hermawan, Wawan (Jurnal Sosio dan Humaniora (SOMA), 2025)
Gen Z is a generation that grew up in the digital era, has different views and preferences towards the world of work compared to previous generations. The credit industry, which includes banking, finance companies, and fintech, is a sector that is increasingly growing along with changes in technology and the public's need for more flexible financial services. Through a descriptive quantitative approach. This study also explores the hopes, motivations, and challenges faced by Gen Z students in preparing themselves for a career in this sector. Then the results of this study also show that Gen Z students prioritize aspects of technology, job flexibility, and opportunities for self-development in choosing a career in the credit industry. They also tend to look for companies that have social and sustainable values, and provide insight for companies in the credit industry to adjust their recruitment and employee development policies according to the needs and expectations of this young generation.